REGULATIONS FOR MOSQUE AND MUSHALA VOICES IN THE PERSPECTIVE OF THEMATIC INTERPRETATION ON VOICE RULE IN WORSHIP - Muhammad Andi Setiawan; Yeti Dahliana (Universitas Muhammadiyah Surakarta, 2022)
Indonesia is a multicultural nation. With the condition of the pluralistic Indonesian society, tolerance is an attitude that must be instilled in order to create harmony between communities. Recently, there has been a polemic regarding the issuance of the Circular Letter of the Ministry of Religion Number 05 of 2022 concerning Guidelines for the Use of Loudspeakers for Mosques and Prayer Rooms by the Minister of Religion Muhammad Yaqut Chalil Qoumas. The purpose of this study is to find out the issue of regulating the use of loudspeakers in terms of using the glasses of Mufassir in Indonesia such as Buya Hamka, M. Quraish Shihab and Muhammad Hasbi ash-Shiddieqy. What is the meaning of tolerance in the Qur'an from the perspective of Indonesian commentators and the regulation of the use of loudspeakers in mosques and prayer rooms. This type of research is a qualitative research using a literature study (library research). The approach used is the character thematic approach. The primary data sources are the book of interpretation of al-Azhar by Buya Hamka, the book of interpretation of al-Misbah by M. Quraish Shihab and an-Nuur by Muhammad Hasbi ash-Shiddieqy. While the secondary data sources are the results of interpretive research on the concept of tolerance and the use of loudspeakers in the Qur'an and other scientific writings.Considering the rules for using loudspeakers for mosques and prayer rooms, the issuance has a good purpose to realize environmental comfort and religious tolerance. So this is in line with what is taught in Islam regarding tolerance, namely mutual respect and openness to existing differences in order to achieve the common good and avoid damage. In this case, lowering the voice in the use of loudspeakers is a form of Islamic tolerance that has been reflected.